POLITIK EKOLOGI KEHUTANAN: KEBIJAKAN HUTAN TANAMAN INDUSTRI DI SAMBELIA, LOMBOK TIMUR - Alfian Hidayat; Purnami Safitri (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2021)
Ecological politics rely solely on economic interest. Development and the environment have a complicated correlation. The industrial plantation forest policy aims to ensure that the economic benefit goes hand in hand with the sustainability demand. Ironically, this policy triggers a conflict between local communities and corporations as the holder of forest concession rights. The concession is practically established due to merely economic interest aligned with the extractive industry of tobacco in Lombok. The plantation is aimed as the supporting source for the tobacco industry since it requires specific woods to roast the tobacco. The study refers to utilizes instrumental state theory and deep ecology perspective to identify how the policy was made for the capital and tobacco capital benefits, while the sustainability objective is left behind. The study shows not only how the concession sparked ironic economic development, but also how the liberal environmentalism approach in industrial forest plantation policy has failed to gain its objective. The economic potential of tobacco in Lombok is the main determinant in industrial forest plantation policy that changes community forests into private forests. In the end, the policy was strategically implemented to sustain production and strengthen corporation monopoly over forests.